A Gandhian answer to the threat of communism? Sarvodaya and postcolonial nationalism in India. (April 2016) - Sherman, Taylor C.
It is an axiom of early postcolonial Indian history that Nehru and his statist conception of nationalism and of economic development dominated the political and economic life of India. As such, scholars have assumed, Gandhian ideas, especially radically non-statist answers to the problems of development, lost influence in this period. This article explores Gandhian economic thinking, in the form of the Bhoodan Movement and three of the thinkers on sarvodaya economics in the 1950s: Vinoba Bhave, K.G. Mashruwala and J.C. Kumarappa. It goes on to demonstrate the complex relationship that these men and their ideas had with Nehru and various levels of the Indian state. It argues that the non-statist ideas remained important in the development of the postcolonial Indian nationalism.